2005
DOI: 10.1038/sj.onc.1208996
|View full text |Cite
|
Sign up to set email alerts
|

Rb plays a role in survival of Abl-dependent human tumor cells as a downstream effector of Abl tyrosine kinase

Abstract: The retinoblastoma (Rb) gene product is a tumor suppressor that is mutated or inactivated in many types of human cancers. Although Rb is known to be an upstream negative regulator of Abl protein tyrosine kinase, we propose here that Rb also functions as a downstream effector of Abl that plays a positive role in survival of Abl-dependent human tumor cells, including Bcr/Abl-positive chronic myelogenous leukemia (CML). We show that Rb is constitutively phosphorylated at tyrosine in Abl-dependent tumor cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Although the mechanism by which BCR-Abl drives leukemiagenesis is well understood, there is little information on the effects of Abl proteins on the development or progression of solid tumors (Singer et al, 2004;Van Diest et al, 2004;Nahta et al, 2005;Nagano et al, 2006;Noren et al, 2006;Vantaggiato et al, 2006). Here, we identify a novel mechanism by which c-Abl promotes breast cancer cell growth and invasion by upregulating ERa expression (Figure 6).…”
Section: Discussionmentioning
confidence: 88%
“…Although the mechanism by which BCR-Abl drives leukemiagenesis is well understood, there is little information on the effects of Abl proteins on the development or progression of solid tumors (Singer et al, 2004;Van Diest et al, 2004;Nahta et al, 2005;Nagano et al, 2006;Noren et al, 2006;Vantaggiato et al, 2006). Here, we identify a novel mechanism by which c-Abl promotes breast cancer cell growth and invasion by upregulating ERa expression (Figure 6).…”
Section: Discussionmentioning
confidence: 88%
“…[130][131][132] In G 0 -G 1 cells, Abl is negatively regulated by pRB where binding inhibits Abl activity by masking the kinase domain. 125,126 Nagano et al 133 observed constitutive tyrosine phosphorylation on Y805 of pRB in chronic myelogenous tumor (CML) cells expressing a constitutively active Bcr/Abl fusion protein. From a functional aspect, phosphorylation of Y805 by Abl in these cells plays a role in cell survival.…”
Section: Regulation Of Prb Function By Cdk3mentioning
confidence: 99%
“…This argument is further supported by observations that apoptosis is induced in CML cells upon knockdown of endogenous pRB. 133 It is puzzling that binding of Abl to pRB blocks Abl kinase activity, and yet in Abl dependent CML cells, pRB is constitutively phosphorylated by Abl. Indeed, Nagano et al 133 observed virtually no phosphotyrosine immunoreactivity in pRB/Abl co-immunoprecipitates from CML cells upon overexpression of pRB, indicating a lack of Abl kinase activity.…”
Section: Regulation Of Prb Function By Cdk3mentioning
confidence: 99%
“…13,14 Rb also plays a key role in the processes of differentiation 13,15,16 and apoptosis. 13,15,[17][18][19] The activity of Rb is regulated by phosphorylation with the phosphorylated form being inactive and the dephosphorylated form active, i.e., only the dephosphorylated and hypophosphorylated forms of Rb bind to E2F transcription factors and block them from activating the transcription of genes crucial for DNA replication and mitosis. 13 The pathways controlling the activity of Rb start from membrane proteins.…”
Section: Introductionmentioning
confidence: 99%